Evaluasi Operasional Pemutus Tenaga Gas SF6 di Gardu Induk 150 kV - Rachmat Sutjipto; Heri Sungkowo; Muhammad Khairan; Slamet Nurhadi; Muhammad Fahmi Hakim (Elposys: Jurnal Sistem Kelistrikan, 2025)
Circuit Breaker (CB) is a critical component in high-voltage substations that functions to switch and disconnect electrical currents under normal and fault conditions. Over time, operational aging and environmental factors may degrade the performance of CB, potentially impacting power system reliability. This study aimed to evaluate the feasibility of 150 kV CB at Probolinggo Substation, particularly in Transformer Bay 1 and Transformer Bay 3, through a comparative analysis of insulation resistance, contact resistance, contact simultaneity, and SF6 gas purity based on tests conducted in 2021 and 2023. The study employed experimental methods and standard-based evaluations, referring to VDE (Catalogue 228/4), IEC 60694, SKDIR-0520/2014, and CIGRE standards. The findings revealed that although insulation resistance values showed slight degradation in 2023, they remained above the minimum threshold, ensuring safe operation. Contact resistance increased marginally due to dust accumulation and aging but still met the IEC 60694 standard. Contact simultaneity remained well within SKDIR-0520/2014 limits, indicating proper switching operation. SF6 gas purity tests showed a minor increase in moisture content due to condensation, yet all parameters complied with CIGRE standards. These results align with previous studies that highlight CB degradation over time but confirm that regular maintenance can sustain its operational reliability. This research underscores the importance of periodic monitoring and predictive maintenance strategies. Future work should explore real-time IoT-based monitoring and numerical simulations to enhance failure prediction models and optimize maintenance strategies for high-voltage circuit breakers.